Using Intersection Conflict Index in Urban Traffic Risk Evaluation. (2016) - Costescu, Dorinela; Raicu, Serban; Rosca, Mircea; Burciu, Stefan; Rusca, Florin
Abstract: This paper presents part of the research on traffic risk estimation for Bucharest City area. The aim of our research is to develop complex models as tools of urban traffic risk assessment in planning phase. In this way, several urban planning alternatives could be analysed and evaluate before important transport infrastructure investment are made. The first part of the paper analyses the state of road accidents recorded in Bucharest. The second part of the paper demonstrates how the intersection conflict index can be used in traffic micro-simulation models to assess measures of traffic risk reducing.